PENGARUH DAYA SAING, KURS, GDP, DAN HARGA TERHADAP EKSPOR KOPI INDONESIA KE LIMA NEGARA (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The purpose this research analyze competitiveness Indonesian coffee in markets and analyze effect exchange rate, GDP, and international prices on coffee exports to markets of five main countries. Data used 2005-2020 time series in United States, Japan, Malaysia and Egypt and analys with Revealed Comparative Advantage (RCA), and Panel Data Regression processing using eviws-12. Based on the analysis RCA method, Indonesia has comparative advantage with RCA value of > 1, Indonesia has strong competitiveness in the five main export destination countries. On simultaneous testing of variabels analys have a significant effect on Indonesian coffee exports in the five main export destination countries. Partially Competitiveness, GDP, and Prices have a positive and significant effect, while the exchange rate variable has a negative and significant effect on the value of Indonesian coffee exports in the five main destination countries. Keywords: Indonesian Coffee, Exchange Rate, GDP, International Prices, RCA.